2023
DOI: 10.1101/2023.01.29.23285153
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Free-Cog reformulated: analyses as independent or stepwise tests of cognitive and executive function

Abstract: Free-Cog is a recently described, hybrid screening instrument incorporating tests of cognitive and executive function. In this study, Free-Cog was reformulated as separate tests of cognitive function and executive function to examine whether this might improve screening accuracy for cognitive impairment (dementia and mild cognitive impairment) compared to the standard, unitary Free-Cog. The two separate tests, designated Free-Cog-Cog and Free-Cog-Exec, were either combined using the Boolean logical AND and OR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This is the combination of outcomes that would be desirable for a screening test for cognitive impairment in older patient cohorts. This outcome might possibly reflect the hybrid nature of Free-Cog as a test of both cognitive and executive functions, since other studies have suggested such a combination may improve detection of neurocognitive disorder [20], although fragmenting the Free-Cog into separate tests of cognitive and executive functions did not suggest better overall performance than the unitary Free-Cog [16]. Other analyses of Free-Cog have previously shown that it fares well in comparison to other short cognitive screening instruments in so-called "metrics of limitation" such as misclassification rate and net harm/net benefit ratio [21].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This is the combination of outcomes that would be desirable for a screening test for cognitive impairment in older patient cohorts. This outcome might possibly reflect the hybrid nature of Free-Cog as a test of both cognitive and executive functions, since other studies have suggested such a combination may improve detection of neurocognitive disorder [20], although fragmenting the Free-Cog into separate tests of cognitive and executive functions did not suggest better overall performance than the unitary Free-Cog [16]. Other analyses of Free-Cog have previously shown that it fares well in comparison to other short cognitive screening instruments in so-called "metrics of limitation" such as misclassification rate and net harm/net benefit ratio [21].…”
Section: Discussionmentioning
confidence: 89%
“…Free-Cog is a hybrid screening instrument of cognition and executive function (item content shown in Table 1, left hand column), purposely designed to have a conversational quality in order to put patients at their ease and hence maximise performance [10]. Free-Cog was used in its standard, unitary formulation, rather than as separate cognitive and executive function tests formulated either sequentially using Boolean logical operators or as a stepwise decision tree, as examined elsewhere [16]. MACE (item content shown in Table 1, right hand column) is a brief cognitive screening instrument derived from the longer Addenbrooke's Cognitive Examination in its third iteration, ACE-III [17].…”
Section: Methodsmentioning
confidence: 99%